2013
DOI: 10.14411/fp.2013.039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mutation and phenotypic expression associated with sulfadoxine-pyrimethamine resistance in Plasmodium falciparum and Plasmodium vivax

Abstract: therapeutic efficacy of sulfadoxine-pyrimethamine (sP), which is commonly used to treat falciparum malaria, was assessed in isolates of Plasmodium falciparum (Welch, 1897) and Plasmodium vivax (grassi et Feletti, 1890) of Aligarh, Uttar Pradesh, North india and taif, saudi Arabia during 2011-2012. Both the species showed mutations in dihydrofolate reductase (DHFr) enzyme as they have common biochemical drug targets. Mutation rate for pfdhfr was higher compared to pvdhfr because the drug was mainly given to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…These findings agree with previously published reports showing low prevalence (less than 5%) of triple and quadruple mutant pvdhfr and pvdhps haplotypes in P. vivax parasite populations from Iran, Pakistan and India (Table 2 ) [ 21 , 22 , 26 – 31 , 36 39 ]. In the wider study region, it was observed that the pyrimethamine resistance marker at position 117 in pvdhfr arose first and was followed by the subsequent mutation in positions 117 and 58, conferring increasing levels of resistance as report earlier [ 23 , 26 – 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings agree with previously published reports showing low prevalence (less than 5%) of triple and quadruple mutant pvdhfr and pvdhps haplotypes in P. vivax parasite populations from Iran, Pakistan and India (Table 2 ) [ 21 , 22 , 26 – 31 , 36 39 ]. In the wider study region, it was observed that the pyrimethamine resistance marker at position 117 in pvdhfr arose first and was followed by the subsequent mutation in positions 117 and 58, conferring increasing levels of resistance as report earlier [ 23 , 26 – 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…India also has high prevalence of double mutations (57%) in P. falciparum dihydrofolate reductase (Pfdhfr) followed by triple (16%; C50R-N51I-S108N; N51I-C59R-S108N, N51I-S108N-I164L, C59R-S108N-I164L; quadruple (10%) (N51I-C59R-S108N-I164L), quadruple (10%; (N51I-C59R-S108N-I164L) and single (7%; A16V, C50R, N51I, C59R, S108N, I164L). Double mutations (C50R-N51I, N51I-C59R, N51I-S108N) have been detected in the Northeastern states, Chhattisgarh, Jharkhand, Odisha, West Bengal and Uttar Pradesh [11][12][13][14][15][16][17]. Even quintuple (three mutations in dhfr (N51I-C59R-S108N) and two mutations in dhps (A437G-K540E) and sextuple resistance (three mutations in dhfr (IRN) and three mutations in dhps (A437G-K540E-A581G) mutations have been reported from the Northeastern states and a few areas in West Bengal between 2006 and 2013 [18].…”
Section: Sulfadoxine-pyrimethamine (Sp) Resistancementioning
confidence: 99%